Positive religious coping acts through perception of nature and silence in its association with well-being and life satisfaction among Polish Catholics - Skalski-Bednarz, Sebastian Binyamin; Konaszewski, Karol; Toussaint, Loren L.; Büssing, Arndt; Surzykiewicz, Janusz (Frontiers in Public Health, 2022)
Previous studies indicate that perceptions of nature and thought-provoking silence can have positive consequences for individual functioning. The purpose of the present study was to assess the relationships between religious coping (assessed with the Brief RCOPE), perceptions of nature and silence (a subscale of the Perception of Change Questionnaire), well-being (the World Health Organization's five-item Well-Being Index) and life satisfaction (the Brief Multidimensional Life Satisfaction Scale). An online questionnaire was completed between 2021–2022 by 1,010 Polish Catholics ages 18 to 73, 61% of whom were women. Structural equation modeling showed that positive religious coping was positively related to well-being (β = 0.08, p = 0.011) and life satisfaction (β = 0.22, p < 0.001). In contrast, negative religious coping was related to reduced well-being (β = −0.07, p = 0.040) and life satisfaction (β = −0.25). In addition, more frequent perceptions of nature and reflective times of silence partially mediated the associations of positive religious coping with well-being (β = 0.04, p = 0.011) and life satisfaction (β = 0.04, p = 0.008). The data might suggest that interventions that help people develop an ability or awareness for nature as an exceptional encounter and may help to strengthen the ways they can utilize their religiosity as a resource and thus contribute to well-being and life satisfaction among Catholics.